NMS obstetrics and gynecology - Pfeifer, Samantha M. (Philadelphia : Wolters Kluwer Health/Lippincott Williams & Wilkins, 2012)
'The book provides up-to-date and relevant information in an easy-to-understand outline format for both students and residents. Basic scientific information is balanced by clinical relevance, and a wealth of more than 200 USMLE-formatted questions allows readers to test their knowledge prior to their board examinations'--
Machine generated contents note: Chapter 1 Endocrinology of Pregnancy Chapter 2 Fetal Physiology Chapter 3 Normal Pregnancy, the Puerperium, and Lactation Chapter 4 Antepartum Care Chapter 5 Identification of the High-Risk Pregnant Patient Chapter 6 Prenatal Diagnosis Chapter 7 Teratology Chapter 8 Substance Abuse in Pregnancy Chapter 9 Antepartum BleedingChapter 10 Labor and Delivery Chapter 11 Intrapartum Fetal Monitoring Chapter 12 Operative Obstetrics Chapter 13 Obste tric Anesthesia Chapter 14 Postterm Pregnancy Chapter 15 Preterm Labor Chapter 16 Hypertension in Pregnancy Chapter 17 Other Medical Complications of Pregnancy Chapter 18 The Gynecologic Office Visit Chapter 19 The Menstrual Cycle Chapter 20 Pediatric and Adolescent Gynecology Chapter 21 Mullerian Anomalies and Disorders of Sexual Development Chapter 22 Amenorrhea Chapter 23 Abnormal Uterine Bleeding Chapter 24 Polycystic Ovary Syndrome Chapter 25 Hirsutism and Hyperandrogenic Disorders Chapter 26 Pelvic Pain Chapter 27 Endometriosis Chapter 28 Uterine Leiomyomas Chapter 29 The Infertile Couple Chapter 30 Ectopic Pregnancy Chapter 31 Recurrent Pregnancy Loss Chapter 32 Family Planning: Contraception and Complications Chapter 33 Sexually Transmitted Diseases Chapter 34 Pelvic Inflammatory Disease Chapter 35 Vulvovaginitis Chapter 36 Disorders of the Pelvic Floor Chapter 37 Menopause Chapter 38 Breast Disease Chapter 39 Gestational Trophoblastic Disease Chapter 40 Pelvic Malignancies Chapter 41 Intimate Partner Violence and Sexual Assault Chapter 42 Medicolegal Considerations in Obstetrics and Gynecology.
This book includes onlines access at http://thepoint.lww.com/pfeifer7e,please refer library staff for the password.
Keywords: Obstetrics -- examination questions; Obstetrics -- outlines; Gynecology -- examination questions; Gynecology -- Outlines